BIOINFORMATICS APPROACH ON ACTION AND MECHANISM OF BROMELAIN IN HEPATOCELLULAR CARCINOMA - S MURTHY, SUSHMA; NARSAIAH T, BALA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to understand biomolecular interactions of Bromelain and its networking with p53 and β-catenin by a computational method of analysis in Hepatocellular carcinoma (HCC) condition. Methodology: The protein interaction partners for p53 and β-catenin involved in the progression of HCC were collected from National Center for Biotechnology Information. We collected data points and standardized the data points for our data analysis from the public database. We used Cytoscape 3.8.2 version plug-in for constructing a Protein-Protein interaction network. We constructed a pathway network using Biorender.com. Results: The protein interactions concerning p53 and β-catenin are identified and a network is constructed. A total of 18 and 34 nodes were identified which are involved in down-regulation and up-regulation of β-catenin and a total of 30 and 27 nodes for homosapiens are identified which are involved in the downregulation and upregulation of the p53 gene. We identified different pathways which trigger and impact the p53 and Wnt/β- catenin signaling pathways as potential target sites for Bromelain to arrest the progression of cancer Conclusion: In conclusion, our in silico studies anti-cancer activity of Bromelain in HCC relating its effect on apoptosis, cell differentiation, mesenchymal transition, p53 signaling, and Wnt/β-catenin signaling pathways.